Efficacy of intranasal vaccination of field buffaloes against haemorrhagic septicaemia with a live gdhA derivative Pasteurella multocida B:2. - O., Rafidah; Saad, Mohd Zamri; Shamsudin, Shahirudin; E., Nasip (BMJ Publishing Group, 2012)

(untitled)
The efficacy of an intranasal haemorrhagic septicaemia vaccine containing live gdhA derivative Pasteurella multocida B:2 was tested in buffaloes in Sabah. Sixty buffaloes, kept grazing in the field with minimal human intervention were devided into three groups of 20 buffaloes per group. Buffaloes of group 1 were exposed intranasal to 5 ml vaccine containing 106 CFU/ml of live gdhA derivative P multocida B:2. Buffaloes of group 2 were not exposed to the vaccine but exposed to PBS and were allowed to commingle and graze in the same field as the buffaloes of group 1 while buffaloes of group 3 were similarly exposed to PBS and were grazing separately. Booster was on group 1, two weeks later. Twelve months after the first vaccination, three buffaloes from each group were brought into the experimental house and challenged subcutaneously with 109 CFU/ml of live wild-type P multocida B:2. All challenged buffaloes of groups 1 and 2 survived with only mild, transient signs while all control unvaccinated buffaloes developed severe signs of haemorrhagic septicaemia and were euthanased between 28 hours and 38 hours postchallenge with signs and lesions typical of haemorrhagic septicaemia. These data showed that the gdhA mutant strain, given intranasally as two doses two weeks apart, successfully induced systemic immunity in exposed buffaloes and also led to spread of vaccine strain to the in-contact animals, where it acted as an effective live vaccine to protect both exposed buffaloes and in-contact buffaloes against challenge with the virulent parent strain.